Birt-Hogg-Dubé Syndrome: Report of a New Mutation - Habib U Rehman (Canadian Respiratory Journal)
Birt-Hogg-Dubé syndrome is an autosomal dominant genodermatosis caused by germline mutations in the folliculin gene and characterized by facial papules, pulmonary cysts, kidney tumours and recurrent pneumothoraces. Several distinct mutations in the folliculin gene resulting in a truncated protein have been described. The present report describes a new mutation, which has not been reported in individuals with Birt-Hogg-Dubé syndrome but is of a type predicted to cause disease.